Implementasi Manajemen Risiko Pada Proyek Pembangunan Sekolah Di Desa Bawolato - Masaati Laoli; Merika Setiawan (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This article discusses the implementation of risk management in development projects as a strategic step to identify, analyze, and control potential risks that can hinder the smooth running and success of a project. Development projects have a high level of complexity and uncertainty, making them vulnerable to various risks such as delays, cost overruns, and substandard quality. Through a systematic risk management approach, projects can anticipate and minimize the negative impacts of these risks. The risk management process, consisting of risk identification, evaluation, handling, and monitoring, has been proven to help improve the efficiency and effectiveness of project implementation. This study emphasizes the importance of involving all stakeholders in the risk management process so that solutions are more appropriate and responsive to field conditions. The study results show that good risk management implementation enables development projects to achieve their time, budget, and quality targets more optimally. Thus, risk management is not only a risk mitigation measure but also a key factor in strengthening the success and sustainability of development projects in today's dynamic era.